2004
DOI: 10.1038/sj.ejcn.1602088
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intake and status in Irish postmenopausal women

Abstract: Suboptimal vitamin D status is common in postmenopausal Irish women during winter. Vitamin D supplementation is associated with improved vitamin D status, even during summertime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
2
30
3
Order By: Relevance
“…In comparison to other healthy Irish population subgroups, which had winter-time serum 25 (OH) D levels assessed the same year and by the same analytical technique for serum 25 (OH) D, the CD patients had relatively similar mean serum 25 (OH) D levels compared to those of 50-to 70-year-old women (mean (s.d. ): 68.6 (34.9), n ¼ 47; Hill et al, 2005a) and 39-to 64-year-old men (mean (s.d. ); 58.8 (22.4), n ¼ 36; Doyle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to other healthy Irish population subgroups, which had winter-time serum 25 (OH) D levels assessed the same year and by the same analytical technique for serum 25 (OH) D, the CD patients had relatively similar mean serum 25 (OH) D levels compared to those of 50-to 70-year-old women (mean (s.d. ): 68.6 (34.9), n ¼ 47; Hill et al, 2005a) and 39-to 64-year-old men (mean (s.d. ); 58.8 (22.4), n ¼ 36; Doyle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to these pathophysiologic factors, other physiological and behavioural factors, which have been shown to be determinants of serum 25 (OH) D levels in healthy adults, may also influence vitamin D status in CD patients. These include age, gender, race, body mass index (BMI), smoking, sunshine habits, Ca intake and vitamin D supplementation (Holick, 1995;Hill et al, 2005b). No previous study has considered the relative importance of pathophysiologic and nonpathophysiologic factors as determinants of vitamin D status in CD patients and how their relative importance may be modulated by season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous small Irish studies reported winter as a significant negative predictor of serum 25(OH)D [17,18]. Studies by Hill et al [16,19] in free-living postmenopausal women showed significantly higher values of serum 25(OH)D during summer than winter.…”
Section: Introductionmentioning
confidence: 95%
“…The intake of vitamin D supplements has been associated with decreases in total mortality rates [12], and in line with international recommendations [13], the Irish public health authorities encourage the uptake by older people of regular vitamin D (and calcium) supplementation [14]. Previous Irish studies suggested that exogenous vitamin D supplementation plays an important role in the prevention of vitamin D deficiency in older people [15,16].…”
Section: Introductionmentioning
confidence: 97%